Variation in leaf attributes and their effects on physiological processes in Leucospermum conocarpodendron L. Buek - Skelton, Robert (Department of Biological Sciences, 2017)
Two subspecies of Leucospermum conocarpodendron with considerable variation in leaf traits occur along the Cape Peninsula along clearly delimited geographical distributions. We attempted to quantify the difference in leaf trait dimensions between green (L. conocarpodendron ssp. viridum) and grey (L. conocarpodendron ssp. conocarpodendron) individuals. Leaves from grey individuals are shown to have higher reﬂectance across the entire photosynthetically active region (PAR) and greater stomatal density. Leaves from grey individuals were found to have higher speciﬁc leaf area (SLA] and a greater size boundary layer. We found no correlation between the transpiration rate and stomatal density, size of the boundary layer and hairiness. We hypothesize that the leaf traits are having an effect on rate of photosynthesis and subsequently determining growth strategy of each type. Grey individuals, because of increased reﬂectance from the leaves are able to persist throughout summer in hot, dry conditions, although they may suffer the cost of reduced photosynthetic rate during late winter and early summer when conditions are relatively mild. Green individuals are able to start growing earlier due to higher SLA and increased rate of photosynthesis but are not able to persist for as long as the grey individuals during mid to late summer. Finally we argue that adaptation to edaphic environment may be associated with subsequent shifts in ﬂowering phenology.